Baicalin Prevents Myocardial Ischemia/Reperfusion Injury Through Inhibiting ACSL4 Mediated Ferroptosis - Zhenyu Fan; Liangliang Cai; Shengnan Wang; Jing Wang; Bohua Chen (Frontiers Media S.A., 2021)
Baicalin is a natural flavonoid glycoside that confers protection against myocardial ischemia/reperfusion (I/R) injury. However, its mechanism has not been fully understood. This study focused on elucidating the role of ferroptosis in baicalin-generated protective effects on myocardial ischemia/reperfusion (I/R) injury by using the myocardial I/R rat model and oxygen-glucose deprivation/reoxygenation (OGD/R) H9c2 cells. Our results show that baicalin improved myocardial I/R challenge-induced ST segment elevation, coronary flow (CF), left ventricular systolic pressure , infarct area, and pathological changes and prevented OGD/R-triggered cell viability loss. In addition, enhanced lipid peroxidation and significant iron accumulation along with activated transferrin receptor protein 1 (TfR1) signal and nuclear receptor coactivator 4 (NCOA4)-medicated ferritinophagy were observed in in vivo and in vitro models, which were reversed by baicalin treatment. Furthermore, acyl-CoA synthetase long-chain family member 4 (ACSL4) overexpression compromised baicalin-generated protective effect in H9c2 cells. Taken together, our findings suggest that baicalin prevents against myocardial ischemia/reperfusion injury via suppressing ACSL4-controlled ferroptosis. This study provides a novel target for the prevention of myocardial ischemia/reperfusion injury.